AL-USHÛL AL-FIKRIYAH WA AL-QADHÂYÂ AL-MANTHIQIYAH LI AL-TADZKÎR WA AL-TA'NÎTS FÎ AL-LUGHAH AL-'ARABIYAH - Damhuri, Damhuri; Bahri, Ratni Bt. H. (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2018)
This article aimed to discuss the theory of mudzakkar and muannats in Arabic. The classification of mudzakkar and muannats is found in most languages, not only in the Smith-Hmit languages family, but also in the Indo-European languages with varying quality and quantity. This linguistic phenomenon is very powerful and is one of the characteristics of the Arabic language. The most popular theory of word grouping into mudzakkar (male) and muannats (females) is a theory seeing a connection and relationship between the word (lafaz) and the meaning (ma’na). In the historical perspective of ancient society, it is also associated with the myths of public belief based on the nature of the world in general consists of mudzakkar and muannats. These theory - in another perspective - especially the ancient society has the power of argument and reason, but in the perspective of modern society has a deadlock of argument and loses its relevance.